2017
DOI: 10.1021/acs.jcim.7b00287
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Binding Pathway of BRACO19 to a Parallel-Stranded Human Telomeric G-Quadruplex Using Molecular Dynamics Binding Simulation with AMBER DNA OL15 and Ligand GAFF2 Force Fields

Abstract: Human telomeric DNA G-quadruplex has been identified as a good therapeutic target in cancer treatment. G-quadruplex-specific ligands that stabilize the G-quadruplex have great potential to be developed as anticancer agents. Two crystal structures (an apo form of parallel stranded human telomeric G-quadruplex and its holo form in complex with BRACO19, a potent G-quadruplex ligand) have been solved, yet the binding mechanism and pathway remain elusive. In this study, we simulated the binding of a free BRACO19 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 76 publications
1
37
0
Order By: Relevance
“… 112 Systematic benchmarking studies up to 1864 crystal complexes have shown that relative MM-GBSA binding energy is a powerful tool to rank ligand binding affinity. 113 117 This is also supported by our previous studies, in which the binding energy of between anticancer drug doxorubicin and a B-DNA fragment (d(CGATCG)2), 98 between anticancer drug daunomycin and a TGGGT G-quadruplex DNA, 118 between RHPS4 and human telomeric G-quadruplexes/duplex, 110 between telomestatin and a hybrid telomeric G-quadruplex, 45 and between BRACO19 and a parallel-stranded telomeric G-quadruplex 119 were successfully assessed by this MM-GBSA protocol.…”
Section: Methodssupporting
confidence: 81%
“… 112 Systematic benchmarking studies up to 1864 crystal complexes have shown that relative MM-GBSA binding energy is a powerful tool to rank ligand binding affinity. 113 117 This is also supported by our previous studies, in which the binding energy of between anticancer drug doxorubicin and a B-DNA fragment (d(CGATCG)2), 98 between anticancer drug daunomycin and a TGGGT G-quadruplex DNA, 118 between RHPS4 and human telomeric G-quadruplexes/duplex, 110 between telomestatin and a hybrid telomeric G-quadruplex, 45 and between BRACO19 and a parallel-stranded telomeric G-quadruplex 119 were successfully assessed by this MM-GBSA protocol.…”
Section: Methodssupporting
confidence: 81%
“…BRACO-19 was optimized from disubstituted acridine derivative, and was first reported as a telomerase inhibitor with an IC 50 value of 115 nM [151]. BRACO-19 can bind to the telomeric G-quadruplex via three binding modes, top stacking, bottom intercalation, and groove binding [171]. The mechanism and anti-tumor activity of BRACO-19 are well studied.…”
Section: G-quadruplex Interacting Compoundsmentioning
confidence: 99%
“…The previously validated FF99SB force field with parmbsc1 and χ OL3+OL15 modifications was applied for G4s. 27,32 The standard Amber parameter (radius 2.658 Å and well depth 0.00328 kJ/mol) and the calibrated parameter (radius 1.705 Å and well depth 0.1936829 kJ/mol) were used for the environmental K + and the ones located between G-tetrad layers, respectively. 24,33 The simulations were conducted by following the same procedure in our previous report.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%